Acurácia de protocolos parciais de exame para avaliação da prevalência e de fatores associados à cárie dentária em crianças de 8 a 12 anos - Dutra, Eduarda Rodrigues (2012)
The aim of this study was to test the accuracy of three partial protocols of oral examination, assessing only first molars, to estimate dental caries prevalence, severity and its association with risk factors. A representative sample of 1,211 children with 8-12 years of age from 20 public and private schools from urban area of Pelotas, Brazil was assessed. DMFT index was obtained by full mouth examination and three partial protocols: P1 all first molars; P2 e P3 first molars from two random diagonal quadrants (1 and 3, 2 and 4). Socioeconomic, behavioral and oral health variables were also collected. Sensitivity, absolute and relative bias and inflation factor were calculated for each partial protocol using dental caries prevalence (DMFT ≥ 1).Risk factors were assessed for all protocols using Poisson Regression for both dental caries prevalence and severity (mean DMFT). Prevalence of dental caries was 32.4% for full mouth examination, 30.2% for P1, 22.2% for P2 and 21.4% for P3. In comparison with full-mouth examination, P1 showed a higher sensitivity [93.1% (CI 95% 91.5; 94.5)]. All protocols showed similar magnitude of association measures for all risk factors investigated, using caries prevalence and mean DMFT. The partial protocols showed potential applicability in epidemiological studies assessing dental caries prevalence and associated factors in schoolchildren aging 8-12 years